ANALISIS FAKTOR INTELEKTUAL DAN NONINTELEKTUAL KEBERHASILAN STUDI MAHASISWA FKIP DI UNIVERSITAS PASIR PENGARAIAN SEBAGAI EVALUASI KINERJA MEMBENTUK LULUSAN GURU YANG BERKUALITA - Afri, Lusi Eka (Edu Research, 2016)
he successfull degree of teachers’ training and education faculty students’ of Pasir Pengraian University in educational process is influenced by Intelectual factor and Non-intelectual factor. Intelligent, interest, and talent are included to intelctual factor. The indicator to indicate it, we can see from report score and educational beackground of students. Non-intelctual factor; such as environment conditions and learning method also influence learning successfull of FKIP UPP students. The conditions of learning environment are like the home status, the large of classroom, the light, and the interaction with the environment. Beside that, the method and learning time also support the learning successfull of FKIP UPP Students’.